(2-4j)x+9+(1+4j)=0

Simple and best practice solution for (2-4j)x+9+(1+4j)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2-4j)x+9+(1+4j)=0 equation:


Simplifying
(2 + -4j) * x + 9 + (1 + 4j) = 0

Reorder the terms for easier multiplication:
x(2 + -4j) + 9 + (1 + 4j) = 0
(2 * x + -4j * x) + 9 + (1 + 4j) = 0

Reorder the terms:
(-4jx + 2x) + 9 + (1 + 4j) = 0
(-4jx + 2x) + 9 + (1 + 4j) = 0

Remove parenthesis around (1 + 4j)
-4jx + 2x + 9 + 1 + 4j = 0

Reorder the terms:
9 + 1 + 4j + -4jx + 2x = 0

Combine like terms: 9 + 1 = 10
10 + 4j + -4jx + 2x = 0

Solving
10 + 4j + -4jx + 2x = 0

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + 4j + -4jx + -10 + 2x = 0 + -10

Reorder the terms:
10 + -10 + 4j + -4jx + 2x = 0 + -10

Combine like terms: 10 + -10 = 0
0 + 4j + -4jx + 2x = 0 + -10
4j + -4jx + 2x = 0 + -10

Combine like terms: 0 + -10 = -10
4j + -4jx + 2x = -10

Add '-2x' to each side of the equation.
4j + -4jx + 2x + -2x = -10 + -2x

Combine like terms: 2x + -2x = 0
4j + -4jx + 0 = -10 + -2x
4j + -4jx = -10 + -2x

Reorder the terms:
10 + 4j + -4jx + 2x = -10 + -2x + 10 + 2x

Reorder the terms:
10 + 4j + -4jx + 2x = -10 + 10 + -2x + 2x

Combine like terms: -10 + 10 = 0
10 + 4j + -4jx + 2x = 0 + -2x + 2x
10 + 4j + -4jx + 2x = -2x + 2x

Combine like terms: -2x + 2x = 0
10 + 4j + -4jx + 2x = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(5 + 2j + -2jx + x) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(5 + 2j + -2jx + x)' equal to zero and attempt to solve: Simplifying 5 + 2j + -2jx + x = 0 Solving 5 + 2j + -2jx + x = 0 Move all terms containing j to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + 2j + -2jx + -5 + x = 0 + -5 Reorder the terms: 5 + -5 + 2j + -2jx + x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 2j + -2jx + x = 0 + -5 2j + -2jx + x = 0 + -5 Combine like terms: 0 + -5 = -5 2j + -2jx + x = -5 Add '-1x' to each side of the equation. 2j + -2jx + x + -1x = -5 + -1x Combine like terms: x + -1x = 0 2j + -2jx + 0 = -5 + -1x 2j + -2jx = -5 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| -3n-2+6n=7n+26 | | 2.97=x+1.6 | | r+.07r=506 | | -3(2y+4)= | | -25x^2+1=0 | | y-4.7=12.52 | | (6c-7d)-(3c+6cd)= | | 2p^2=-4p+1 | | -4x+2=-6 | | 42x-12x^2=0 | | 5x+11=2(4x+7) | | 3s-(0.5s+7.2)=32.8 | | 40y-40=-40+40 | | M=j-k | | -7-(-3-2g)-10=0 | | 7-5x=27 | | b^4=48 | | 4x+4(x+9)=20 | | y^2-10y+2x+25=0 | | (5a^3+6a)+(-3a^2-5a)= | | 2m-14=6 | | 5(3x+7)-(4x-6)=12 | | 5k-13=2k+2 | | (4+3x+x^2)+(6-9x+x^2)= | | 4t+9=-9t-13 | | -3(1+w)+4w=8 | | -6x+36=28 | | 8-(2x-6)=22 | | 4+8y+9n-2y-2n-17= | | -p^2+8p+4= | | 4z+3(z+7)=-14 | | 2(x-2y-7z)= |

Equations solver categories